Microorganisms of genus Trichoderma as phytohormone promoters and pathogen suppressors (Bioagro, 2022)
Chemical products applied indiscriminately in agriculture have caused serious imbalances to the environment; thus, there is a need to use sustainable tools such as bioinoculants. Five strains of Trichoderma spp. were evaluated as producers of organic acids, auxins and gibberellins, as well as the radial growth inhibition percentage (RGIP) and its antagonistic capacity against plant pathogens such as Fusarium oxysporum, Alternaria spp. and Helminthosporium spp. Results showed that all strains segregated organic acids and the maximum production was attained at 72 hours; TJ7 (143.46 mm), TJ3 (138.07 mm), TM (130.71 mm), TB (126.88 mm) and TF (109.48 mm). All of them synthetized auxins and gibberellins. TF showed a higher production of the first ones (35.3 μg∙mL-1), and no statistical differences were found on the second ones (P≥0.05). The highest value of RGIP against Fusarium oxysporum was obtained on TB (83.3 %) and TJ3 (81.5 %), all descending values against Alternaria spp, were in the following order: TB (87.7 %), TJ3 (87.6 %), TJ7 (87.2 %), TF (87.0 %) and TM (86.7 %) while TJ3 reached the highest value (76.6 %) against Helminthosporium spp. The evaluated strains showed class 1 and 2 of antagonistic capacity against plant pathogens (values 1.0 to 2.0) according to the scale of Bell et al. (1982), showing that they have the potential to be tested under greenhouse or open field conditions as biological control agents and/or plant growth promoters, their combination could play a promising role as a biotechnological product and a sustainable tool in agricultural areas of Northern Mexico.
Keywords: Alternaria; Fusarium; Helminthosporium; plant growth regulators